Three-Year Outcomes With the Multilayer Flow Modulator for Repair of Thoracoabdominal Aneurysms: A Follow-up Report From the STRATO Trial. (October 2016) - Vaislic, Claude D.; Fabiani, Jean Noël; Chocron, Sidney; Robin, Jacques; Costache, Victor S.; Villemot, Jean-Pierre; Alsac, Jean Marc; Leprince, Pascal N.; Unterseeh, Thierry; Portocarrero, Eric; Glock, Yves; Rousseau, Hervé; et al.
Purpose: To evaluate midterm outcomes of endovascular repair of types II and III thoracoabdominal aortic aneurysms (TAAA) using the Multilayer Flow Modulator (MFM) in patients unsuitable for open surgery or fenestrated stent-grafts.Methods: In the prospective, multicenter, nonrandomized STRATO trial (EudraCT registration: 2009-013678-42; ClinicalTrials.gov identifier NCT01756911), 23 patients (mean age 75.8 years; 19 men) with Crawford type II and III TAAA (mean diameter 6.5 cm) were implanted between April 2010 and February 2011. Outcomes included all-cause mortality and stable aneurysm thrombosis with associated branch vessel patency.Results: Through 36 months, there were 7 deaths (none confirmed as aneurysm-related), and no cases of spinal cord injury, device migration or fracture, or respiratory, renal, or peripheral complications. Three patients were lost to follow-up and 2 devices were explanted. The device was patent in the 11 remaining patients at 3 years. Stable aneurysm thrombosis was achieved for 15 of 20 patients at 12 months, 12 of 13 at 24 months, and 10 of 11 at 36 months. The rate of branch patency was 96% at 12 months (primary patency), 100% at 24 months, and 97% at 36 months. Nine patients suffered from endoleaks (attachment site or device overlap); 9 patients underwent 11 reinterventions (3 surgical). Maximum aneurysm diameter was stable for 18 of 20 patients at 12 months, 11 of 13 at 24 months, and 9 of 11 at 36 months. For 10 patients with computed tomography at 36 months, the mean ratio of aneurysm flow volume to total volume had decreased by 83%; the mean ratio of thrombus volume to total volume increased by 159%.Conclusion: Through 3 years, endovascular repair with the MFM appears to be safe and effective while successfully maintaining branch vessel patency.